2010
DOI: 10.1016/j.ejcts.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Awake video-assisted pleural decortication for empyema thoracis☆

Abstract: In our study, awake video-assisted pleural decortication proved feasible and resulted in satisfactory lung re-expansion in 95% of the patients. We hypothesise that spontaneous ventilation facilitated both identification of the correct plane and dissection, thus resulting in lesser surgical injury on the underlying lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…Similar results came from Cajozzo et al (27). Finally in a controlled study from Tacconi et al (40), no substantial difference in morbidity rate was found with either NIVATS or GAVATS decortication for stage II pleural empyemas.…”
Section: High-risk Patientssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results came from Cajozzo et al (27). Finally in a controlled study from Tacconi et al (40), no substantial difference in morbidity rate was found with either NIVATS or GAVATS decortication for stage II pleural empyemas.…”
Section: High-risk Patientssupporting
confidence: 71%
“…Other non-randomized studies reported significant differences in hospital stay in the settings of pleural effusion (27,40), pulmonary metastasectomy (42) and secondary PNX (36). On contrary, Wu et al (33) in their study on NIVATS lobectomy in a geriatric population failed to demonstrate any difference in hospital stay length (33).…”
Section: Hospital Staymentioning
confidence: 94%
“…During more than a decade this program achieved a consistent amount of knowledge about the surgery in awake patients and produced a great number of scientific publications (68,69,81,84,(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). In our program we initially privileged anesthesia delivered through an epidural catheter with a fully awake and collaborative patient (96)(97)(98)(99). In this way we achieved the neurological surveillance that we consider a physiological pattern of monitoring.…”
Section: The Awake Anesthesia In Progressmentioning
confidence: 99%
“…In MVATS anesthetic management entailed maintenance of spontaneous ventilation and either a thoracic epidural catheter inserted at the T4-T5 level (6)(7)(8)(9)(10) or intercostal injection of lidocaine 2% plus ropivacaine 7.5% at the site(s) of surgical incision for thoracic analgesia. Physiologic patient monitoring included radial artery catheterization, bispectral index monitoring, and a capnograph stuck to a nostril for real-time end-tidal CO 2 assessment.…”
Section: Anesthesia and Surgical Techniquementioning
confidence: 99%
“…In addition, other methodological and technological advances including uniportal surgical approaches and the use of small-sized instrumentation are being adopted in order to minimize the overall invasiveness of VATS thus defining novel minimalist surgical strategies (MVATS) (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%